The possibility of change - Sibbald, B. (Canadian Medical Association journal (CMAJ), 2008)
Dr. James Orbinski's humanitarian drive has taken him from the board rooms of the World Health Organization to the Rwandan genocide, from co-founding Médecins Sans Frontières Canada (1991) to accepting the Nobel Peace Prize as Médecins Sans Frontières' international president (1999). Now, the Canadian physician has written An Imperfect Offering and is the subject of Triage, a new documentary film (see pages 1191 and 1192) about his engagement with the developing world for more than 16 years. Orbinski: For clinicians, where one sees impediments to access to health ... where one sees patients not getting the health care they need, physicians have a responsibility to speak about that and to speak about it in a public setting - whether they are in Moose Jaw, Rwanda or Tuktoyaktuk, it doesn't matter. Yesterday there was an article about the state of Ohio [which] has now set up a lottery for people to get access to health care. There are 80 000 applicants. There are 600 000 people in Ohio who do not have health care insurance. Their political system has reduced the issue of access to health care to a lottery. ... In my view we have the responsibility to elevate the issue of access to health care to something beyond that. I mean it's a fundamental political choice and it's a fundamental choice around how we see ourselves in relationship to others, and ... how we see the dignity of others. the suffering of another person and of the pursuit of health of another person. Orbinski: Under very specific circumstances, that's absolutely true. And in certain other circumstances, for example war crimes or crimes against humanity or genocide, there's no such thing as ... moral neutrality. In those circumstances there are violations of the laws of war and the laws that are themselves determined politically. So if you are going to speak against violation of law, you are engaging in a political act by definition because you're demanding that the law be enforced. And in situations of war crimes, crimes against humanity and genocide, in my mind silence is virtually criminal. So you must speak in those circumstances.